Read this if you want to take great photographs - Carroll, Henry (London : Laurence King Pub. Ltd., 2014)
Walks through the basics of composition, exposure, light, lenses, and seeing, illustrating points and techniques with images taken by master photographers.
Composition -- Exposure -- Light -- Lenses -- Seeing.
Includes index.
Keywords: Photography -- Technique; Composition (Photography); Photography -- Exposure